Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2320/matertrans.mk201619
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Application of Electrochemistry to the Extraction of Titanium and Its Applications

Abstract: For over ve decades the main route for the extraction of titanium has been the Kroll process. It is regarded as being expensive, labour intensive, reliant on a high quality feedstock, and environmentally unfriendly, but it has thus far not been possible to replace it. As a result the usage of titanium is still restricted to a few high end applications. During the past twenty years several new molten salt based electrochemical approaches for the reduction of titanium oxide have been introduced to meet these cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…R5) and carbon dioxides (CO 2 ) can react with O 2À ions in the molten salt to form carbonate ions (CO 3 2À ) which can then transfer to, and be reduced to carbon at the cathode. 22,54,72 These parasitic reactions lower the current efficiency and cause contamination to the cathodic products via, e.g., carbide formation. 22 When evolving gases, the carbon anode may also release carbon debris that float on the molten salt surface and potentially short circuit the cell, further impairing the current efficiency.…”
Section: Towards the Processes Sustainability A Carbon-free Titanium mentioning
confidence: 99%
See 3 more Smart Citations
“…R5) and carbon dioxides (CO 2 ) can react with O 2À ions in the molten salt to form carbonate ions (CO 3 2À ) which can then transfer to, and be reduced to carbon at the cathode. 22,54,72 These parasitic reactions lower the current efficiency and cause contamination to the cathodic products via, e.g., carbide formation. 22 When evolving gases, the carbon anode may also release carbon debris that float on the molten salt surface and potentially short circuit the cell, further impairing the current efficiency.…”
Section: Towards the Processes Sustainability A Carbon-free Titanium mentioning
confidence: 99%
“…22,54,72 These parasitic reactions lower the current efficiency and cause contamination to the cathodic products via, e.g., carbide formation. 22 When evolving gases, the carbon anode may also release carbon debris that float on the molten salt surface and potentially short circuit the cell, further impairing the current efficiency. 59 Thus, by replacing carbon with an inert material, pure oxygen can evolve as the only anodic off-gas (cf.…”
Section: Towards the Processes Sustainability A Carbon-free Titanium mentioning
confidence: 99%
See 2 more Smart Citations
“…A new Ti production process replacing the Kroll process is desired. Many researchers have been studying the innovative smelting process, [1][2][3][4][5][6][7] but those processes are still under development. In our laboratory, the direct electrowinning of liquid Ti has been studied in molten fluoride, and it was shown that Ti metal was obtained.…”
Section: Introductionmentioning
confidence: 99%